Biomechanical Behaviour of Oro-maxillofacial Prostheses (Mathematical Modeling in Oro-maxillofacial Sphere) - Ady Garfunkel; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2010)
The tumor pathology resulted in substance losses and the traumas at facial level are only several aspects that mark patients in a mutilating way, modifying significantly and sometimes irreversibly their behavior, turning them from active, social people into isolated ones. A prosthesis and so much the more an obturator shall not be worn unless they remake the lost functions and are accepted by the sick person from the psychic viewpoint. The final goal of treatment follows the improvement of sick person's life quality and represents a psychological support both for them and their family. The losses of intra-oral substance are solved in the clinical register by means of augmentation biomaterials of the Bio Oss type. As for the losses of extra-oral substance, they are solved following the mathematical modeling by applying simple pressure at the prosthesis level or by fixing the prosthesis with four magnets that were attached beforehand to the bone. The substance losses represent a complex pathology, the contribution of the filling materials, the prosthetic means correlated to the particularity of the clinical case are essential for a successful clinical finality. We may not speak of a successful prosthetic implant if we do not pay a special attention to the mucous-bony deficit by specific prosthetic techniques.